Politik Hukum tentang Pembatasan Upaya Hukum Peninjauan Kembali terhadap Pejabat/Badan Tata Usaha Negara Berdasarkan Putusan Mahkamah Konstitusi Nomor 24/PUU-XII/2024: Perspektif Siyasah Qadhaiyyah - Mochamad Suwanda Hadiansyah; Bobang Noorisnan Pelita; Lutfi Fahrul Rizal (Jurnal Hukum Lex Generalis, 2025)
This research seeks to analyze the legal politics and principles of Siyasah Qadhaiyah regarding the Restrictions on Judicial Review of Officials or State Administrative Bodies since the issuance of Constitutional Court Decision Number 24/PUU-XII/2024. MK Aquo's decision has significantly changed the legal framework regarding the right of state administrative bodies or officials to submit a judicial review (PK). To answer this question, this research uses a normative juridical approach, by reviewing legal documents, jurisprudence, and scientific works to explore legal ratios, legal consequences and siyasa qadhaiyah views on this decision. The results of the research show that, firstly, giving the right/authority to the TUN Agency/Official to submit a judicial review of a decision that has already been made is counterproductive and has the potential to cause legal uncertainty, so that MK Aquo's decision is a progressive decision that can protect the public seeking justice and legal certainty. Second, even though the Constitutional Court Aquo Decision is a binding and final decision (final and binding), there is a need for follow-up by the decision address because the Constitutional Court Aquo decision is non-self implementing, the three contents of the Constitutional Court Aquo Decision are relevant to the concept of siyāsah qaḍhā'iyyah, especially values. which is adhered to by the Islamic judiciary of al-maẓhālim region